Single port laparoscopic transabdomional preperitoneal inguinal hernia repair: prospective cohort study - Pal Singh Sodhi, Tejinder; Savyasacchi Goyal, Kirti; Garg, Utkarsh; Goel, Kritesh; Gandhi, Hemangi (International Surgery Journal, 2019)
Background: Laparoscopic inguinal hernia repair offers variety of advantages than the conventional repair. Therefore, laparoscopic transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) techniques are frequently preferred. Single-incision laparoscopic surgery (SILS) was developed with the aim of reducing the invasiveness of conventional laparoscopy and has been successfully performed by many surgeons. Methods: This study was conducted on 25 patients over a period of one year from November 2011 to October 2012 in Department of General Surgery, Acharya Sri Chander College of Medical Sciences and Hospital, Sidhra, Jammu (ASCOMS), India with uncomplicated inguinal hernia which underwent single port laparoscopic TAPP (SPL-TAPP). Results: In this study, all the patients (100%) had unilateral inguinal hernia, among them 16 (64%) had direct and 9 (36%) had indirect inguinal hernia. Pediatric patients were excluded from study. The mean age, weight and height were 44.4, 59.46 and 157.2 cm respectively. Intraoperative data for SPL-TAPP had complications in 1 case (seroma formation) and need for conversion to conventional surgery was also seen in 1 case. Conclusions: Single port TAPP offers to be safe and efficacious with minimum re-occurrences and shorter hospital stay.